Efficacy of mindfulness- and acceptance-based cognitive-behavioral therapies for bodily distress in adults: a meta-analysis - Maas genannt Bermpohl, Frederic; Hülsmann, Lea; Martin, Alexandra (Frontiers in Psychiatry, 2023)
Objective: Bodily distress, i.e., somatoform disorders and associated functional somatic syndromes, is highly prevalent, often persistent and highly disabling. It has been proposed that “third wave” therapies may be beneficial variants of cognitive behavioural treatments. However, evidence on their efficacy is scarce. This meta-analysis examines the efficacy of “third wave” psychotherapies (mindfulness-based cognitive therapy [MBCT], mindfulness-based stress reduction [MBSR], and acceptance and commitment therapy [ACT]) in adults with bodily distress. Method: We included randomized controlled trials (RCTs) treating adults with bodily distress using MBCR, MBSR, and ACT compared to inactive and non-specific control groups. A random effects model was used. The primary outcome was somatic symptom severity. Secondary outcomes were degrees of depression and of anxiety, health anxiety, perceived health status, mindfulness, psychological inflexibility, and pain acceptance. Results: Sixteen RCTs with 1288 participants were included in the analysis (k = 4 MBCT, k = 7 MBSR, k = 5 ACT; k = 7 fibromyalgia, k = 5 irritable bowel syndrome, k = 1 chronic fatigue syndrome, k = 2 bodily distress, k = 1 medically unexplained symptoms). However, not all studies provided data for each of the relevant outcomes. The analyses revealed that “third wave“ therapies were more effective than control conditions in reducing somatic symptom severity (k = 15, n = 1100, g = -0.51, 95%CI -0.69; -0.32). Heterogeneity was moderate (I² = 52.8%, 95%CI 15.1 to 73.8). Effects for secondary outcomes were small to moderate with varying degrees of heterogeneity. We did not find differences between the different therapy approaches (mindfulness- vs. acceptance-based therapies); neither therapy dosis (i.e., total duration of therapy sessions) nor number of sessions were significant moderators of efficacy. Conclusions: The therapies addressing mindfulness and acceptance proved to be more effective than control conditions. Hence, they are promising treatment approaches for bodily distress. However, there is still need for research on which patient groups may benefit from these psychological approaches.